ANALYSIS OF DEMAND CURVES IN THE STOCK AND FINANCIAL MARKETS OF MONOPOLISTIC COMPETITION - M. I. Geras’kin; V. V. Manakhov (Russian Journal of Economics and Law)
Objective: to identify patterns of monopolistic competition as applied to markets of household appliances, consumer loans and insurance products in Russia. Methods: econometric modeling, trending, regression analysis, analysis of statistical significance. Results: the statistical analysis of trends in the market of household appliances, insurance and credit markets has been carried out; the statistical significance and adequacy of the models has been assessed; adequate and accurate regression models of price trends of household appliances and electronics have been developed, as well as of the interest rates of consumer loans and insurance rates for loan debts. Scientific novelty: the actual patterns of decreasing demand curves for household appliances, consumer loans and insurance products were found for the relevant markets in the Russian Federation in 2009-2014. Practical significance: the model can be used for solving problems of optimal planning strategies of retailers, insurers and banks.